Material Content of Income Redistribution Concept in Social Studies Subject - Jahidah Jahidah; Ersis Warmansyah Abbas; Jumriani Jumriani; Mutiani Mutiani; Ismi Rajiani (The Innovation of Social Studies Journal, 2023)
The subject matter of income redistribution in social studies learning is not only delivered based on one source. However, it can be developed by utilizing various accurate sources in the surrounding environment, especially in the material of income redistribution teachers can develop students' understanding by looking at differences in income in the environment caused by inequality of distribution which is given. This study aims to provide an understanding of students by utilizing environmental sources as examples of learning. The research method was compiled using a literature study by utilizing and collecting several books, journals, and other relevant library sources according to the issues contained. The search used keywords using Google Scholar and e-books in pdf and full-text format. The results of this study explain that the material for income redistribution needs to be developed more by incorporating and connecting learning themes into real life and the surrounding environment that occur as an example in learning at school so that students more readily understand lessons and are more active in getting to know their surroundings.